Predictors of Attitude and Intention to Use E-recruitment among Human Resource Management Practitioners in the Province of Romblon - Fetalvero, Sherryll (Romblon State University Research Journal, 2024)
This study determined the perceptions of the human resource management (HRM) practitioners in the province of Romblon about e-recruitment. Significant predictors of their attitude and intention to use e-recruitment were also analyzed using the Technology Acceptance Model (TAM). Variables such as age, sex, years of experience as an HRM practitioner, awareness of e-recruitment, proficiency in technology use, perceived ease of use, perceived usefulness and attitude towards e-recruitment were tested. Thirty-one HRM practitioners were surveyed online using a modified questionnaire on e-recruitment perceptions. Results revealed that the respondents have highly favorable perceptions about e-recruitment. Their attitude towards e-recruitment was mainly influenced by their perceptions of ease of use and usefulness (R2=66.7%). On the other hand, their intention to use e-recruitment is influenced by their attitude towards this technology, their awareness of it, and their length of experience as HRM practitioners (R2=84.9%). Findings also show that Facebook is the top platform used in e-recruitment which supports the emerging trend on what scholars dub as social recruitment. For agencies planning to automate the recruitment process, the platform must be perceived to be easy to use and useful to foster a positive attitude and better intention to use the e-recruitment technology. HRM practitioners are encouraged to keep abreast and aware of the HRM-related technologies in their field towards a better and improved HRM system in general.